Chemistry and biology of microsomal prostaglandin E2 synthase-1 (mPGES-1) inhibitors as novel anti-inflammatory agents: recent developments and current status. Issue 34 (17th March 2016) - Khurana, Puneet; Jachak, Sanjay M.
Abstract : Prostaglandin (PG) E2, a key mediator of inflammatory pain and fever, is biosynthesized from PGH2 by mPGES-1. Abstract : Prostaglandin (PG) E2, a key mediator of inflammatory pain and fever, is biosynthesized from PGH2 by microsomal prostaglandin E2 synthase-1 (mPGES-1). During inflammation the expression of mPGES-1 increases resulting in increased PGE2 formation. Specific inhibition of mPGES-1 reduces the biosynthesis of PGE2, sparing other physiologically important PGs such as prostacyclin (PGI2 ) and thromboxane A2 (TXA2 ). Inhibition of mPGES-1 might be superior over the inhibition of cyclooxygenases (COX), as the latter leads to the suppression of PGI2, TXA2 along with the pathogenic PGE2 resulting in gastro-intestinal, renal and cardiovascular complications. Therefore, inhibition of mPGES-1 has been proposed as a promising approach for the development of drugs for inflammation and pain therapy, which only suppresses PGE2 biosynthesis, avoiding the side effects caused by nonsteroidal anti-inflammatory drugs (NSAIDs) and specific COX-2 inhibitors. The current review article includes natural and synthetic inhibitors of mPGES-1 reported since 2000 with their in vitro activity (IC50 values), in vivo activity, the status of clinical candidates, and critical appraisal of these reported inhibitors.